Functional Outcome of Total Hip Arthroplasty in Steroid-Induced Avascular Necrosis Among COVID-Recovered Patients - Dr V Ratan Singh Naik; Dr Sandeep Saraf; Dr Krishna Agarwal (International Journal of Pharma and Bio Sciences, 2023)
Osteonecrosis or Avascular Necrosis (AVN) of the femoral head is a disabling condition in young individuals. The number of cases has significantly increased after the COVID-19 pandemic. The use of corticosteroids in treating COVID-19 may have contributed to the developing of AVN in young patients. Aggressive presentation and rapid progression of osteonecrosis have been implicated as risk factors for total hip arthroplasty. Early management of osteonecrosis of the femoral head (ONFH) entails joint preservation procedures, antiresorptive therapy, and reduced weight bearing. THR should be performed only as a last resort due to the aggressive progression of ONFH to severe and incapacitating osteoarthritis. There is a definite risk of contralateral hip affection, and the pathophysiology of varying affections is still unclear. Due to the early presentation and young age of patients at the time of surgery, there is a need for continuous monitoring. Hence there is a need for continuous research in this area. The study aims to know the effectiveness of total hip replacement (THR) for femoral head osteonecrosis among COVID-19-affected patients. Objectives are to identify symptomatology, limitation of functional hip range of movements, plain radiography findings, Ficat -Arlet staging, and to determine the functional outcome following THR by quantification through mean VAS score and modified-HHS score. The key findings of our study are A) there is a steady risk of progression of AVN to secondary osteoarthritis, which entails the need for THA, B) In unilateral involvement, with no affection in the uninvolved hip (nascent hip) at the initial presentation the disease does not progress, whereas those involved hips with low-grade AVN can progress to Highgrade C) There is a greater acceptability of THR as a definitive procedure with good to excellent functional outcome.